Molecular Cytogenetic Characterization of Novel Wheat-rye T1RS.1BL Translocation Lines with High Resistance to Diseases and Great Agronomic Traits - Ren, Tianheng; Tang, Zongxiang; Fu, Shulan; Yan, Benju; Tan, Feiquan; Ren, Zhenglong; Li, Zhi (Frontiers in Plant Science, 2017)
Rye has been used worldwide as a source for the genetic improvement of wheat. In this study, 2 stable wheat-rye primary T1RS.1BL translocation lines were selected from the progeny of the crossing of the wheat cultivar Mianyang11-1 and a Chinese local rye variety, Weining. These 2 novel translocation lines were identified by molecular cytogenetic analysis. PCR results, multi-color fluorescence in situ hybridization (MC-FISH), and acid polyacrylamide gel electrophoresis (A-PAGE) indicated that both new translocation lines harbor a pair of T1RS.1BL translocation chromosomes, and have been named RT828-10 and RT828-11, respectively. The cytogenetic results also indicated that the pSc119.2 signals of 5AL were absent in both lines along with the pSc119.2 signals of 4AL of RT828-11. When inoculated with different stripe rust and powdery mildew isolates, both lines expressed high resistance to Puccinia striiformis f. sp. tritici and Blumeria graminis f. sp. tritici pathotypes, which are prevalent in China and are virulent on Yr9 and Pm8. The line RT828-11 also exhibited excellent agronomic traits in the field. The present study indicates that this rye variety may carry untapped variations that could potentially be used for wheat improvement.